Clima familiar deportivo y nivel de actividad física en adolescentes (Sports family climate and the level of physical activity in adolescents) - Concha-Cisternas, Yeny; Gomez, Barbara; González, Aylen; Pasten, Estefani (Retos, 2022)
Se ha reportado que el nivel de actividad física (AF) de los adolescentes estaría influenciado por el clima familiar deportivoObjetivo: Analizar la relación entre el clima familiar deportivo y el nivel de AF en adolescentes. Métodos: La muestra de este estudio comprendió a 100 adolescentes entre 13 y 18 años. Se utilizó el cuestionario de Clima Familiar Deportivo y el cuestionario Physical Activity Questionnaire for Adolescents (PAQ-A) para medir el nivel de AF. Para establecer el nivel de relación entre las variables se realizó una correlación de Pearson y se utilizó un coeficiente de correlación r. Además se utilizó la prueba de Chi cuadrado para establecer asociaciones. Resultados: Se obtuvieron relaciones estadísticamente significativas entre las dimensiones apoyo (p=0,001 r=0,46),  interés (p=0,018; r=0,236), comunicación (p=0,002; r=0,308) y educación (p=0,001; r=0,328) con el nivel de AF. No hubo asociaciones entre nivel de escolaridad de los padres con el nivel de AF de los adolescentes. Conclusión: Este estudio confirma que existe relación entre el clima familiar deportivo y el nivel de actividad física en adolescentes de la muestra estudiada.Abstract. Introduction: It has been reported that the level of physical activity (PA) of adolescents would be influenced by the sports family climate. Aim: To analyze the relationship between the sports family climate and the level of PA in adolescents. Methods: The sample of this study comprised 100 adolescents, aged between 13 and 18 years. The Sports Family Climate questionnaire was used and the Physical Activity Questionnaire for Adolescents (PAQ-A) questionnaire to measure the level of PA. To establish the level of relationship between the variables, a Pearson correlation was performed and a correlation coefficient r was used to establish the level of correlation. In addition, the Chi square test was achieved to establish associations. Results: Statistically significant relationships were obtained between the support dimensions (p = 0.001 r = 0.46), interest (p = 0.018; r = 0.236), communication (p = 0.002; r = 0.308) and education (p = 0.001; r = 0.328) with the level of physical activity. There were no associations between the level of education of the parents and the level of PA of the adolescents. Conclusion: This study confirms that there is a relationship between the sports family climate and the level of physical activity in adolescents of the studied sample level of physical activity in adolescents.